The effect of language discordance on the experience of palliative care: A scoping review - Shawn P. Dookie; Lynn Martin (PLoS ONE, 2025)
Background Internationally, research demonstrates consistent disparities in access to palliative care services for those in underserved communities with life-limiting conditions. Objectives This outcomes-oriented scoping review examines the impact of language discordance on palliative care (PC) experiences. It seeks to answer the question: what are the PC experiences of individuals who do not speak the same language as their care provider? The review explored the range and depth of existing research and synthesizing trends across studies. Design Online databases were used to find articles published in English or French, from January 1, 2010, to February 5, 2024. Inclusion criteria included studies that explored the relationship between palliative, end-of-life or hospice care, as well as advance care planning in the context of language discordance between individual and health care provider. This scoping review was originally designed to explore Canadian official language minority communities, but was broadened to an international search for a more robust dataset. Results A total of 39 articles were included in the review, 23 qualitative studies, nine quantitative studies and seven mixed-methods studies. The following elements were extracted from eligible articles: country, study design, target population and definitions, participant characteristics, definitions of PC, outcomes studied, findings related to the study aims, as well as author-defined study limitations and next steps. Areas for further research were identified, as were areas for policy and practice change. Studies used various perspectives of PC, often synonymizing it with end-of-life and hospice care, as well as advanced care planning. There was no contextual definition of language barriers in the studies and no studies that explored the PC in any Canadian official language minority communities. The importance of in-language resources, accessibility of skilled interpreters, education in cross-cultural care were all common themes in the literature. Conclusions From a variety of perspectives, studies generally found that language discordance has a negative impact on the quality of accessibility of palliative, end-of-life and hospice care, as well as advanced care planning. Given that Canada’s population is becoming increasingly linguistically diverse, there is a need to better understand the impact of receiving PC from individuals who speak another language on both the quality of PC and quality of life at the end of life.